(untitled) (Contemporary Journal of Social Science Review, 2025)
This study investigates task types’ impact on creativity in ESL learners’ writings. The research design used for the study was a mixed-method approach. To ensure the impact of task type on creativity in writing of ESL learners, 50 undergraduate students (males=10, females=40) from different departments were selected by convenience sampling. Two writing tasks were performed, one was imaginative writing and the other was picture interpretation. Writing tasks were marked according to the “Torrance Test of Creative Thinking (TTCT) rubric. One sample t-test was used to compare the results of both writing tasks. Results showed that there is a statistically significant difference between the mean scores of both tasks indicating that there is an impact of task type on creativity in the writings of ESL learners. These findings have significance for educators and curriculum designers as they highlight the need to add creative writing projects in ESL language training to foster students’ creativity.